Модели и инструментальные средства формирования и анализа свойств случайных последовательностей - Ставицкая, Е. С.; Саранча, С. Н. (Weber, 2010)
The three methods of random and pseudorandom numbers generation are considered and software means for random sequence logging and analysis are proposed.
Keywords: анализ свойств случайных последовательностей